Identification by culture, PCR, and immunohistochemistry of mycoplasmas and their molecular typing in sheep and lamb lungs with pneumonia in Eastern Turkey - Kilic, Ayse; Kalender, Hakan; Eroksuz, Hatice; Muz, Adile; Tasdemir, Bulent (Springer, 2013)
This study used cultures, polymerase chain reaction (PCR), and immunoperoxidase to examine samples from 216 lungs from sheep and lambs with macroscopic pneumonia lesions for the presence of Mycoplasma species. DNA was extracted from lung tissue samples and broth cultures with the help of a DNA extraction kit and replicated using genus-specific and species-specific primers for mycoplasma. The lung samples were examined by the immunoperoxidase method using hyperimmune Mycoplasma ovipneumoniae serum. The randomly amplified polymorphic DNA (RAPD) test was used for the molecular typing of M. ovipneumoniae isolates. Mycoplasma was isolated in the cultures of 80 (37.03 %) of a total of 216 lung samples. Genus-specific mycoplasma DNA was identified by PCR in 96 (44.44 %) samples in broth cultures and 36 (16.66 %) directly in the lung tissue. Of these 96 cases in which genus-specific identification was made, 57 (59.37 %) were positive for reaction with species-specific primers for M. ovipneumoniae and 31 (32.29 %) for Mycoplasma arginini. The DNA of neither of the latter two species could be identified in the remaining eight samples (8.33 %) where mycoplasma had been identified. As for the immunoperoxidase method, it identified M. ovipneumoniae in 61 of 216 lung samples (28 %). Positive staining was concentrated in the bronchial epithelium cell cytoplasm and cell surface. RAPD analysis resulted in 15 different profiles. Our results suggest that PCR methods could be successfully used in the diagnosis of mycoplasma infections as an alternative to culture method and identifying this agent at the species level.
Keywords: M. ovipneumoniae; PCR; Culture; Pneumonia; Sheep; Lamb